Combination of two odour chemical lures does not increase thrips capture in field bioassays - Teulon, D.A.J.; Nielsen, M-C.; James, D.E.; Winkler, S.; Mclachlan, A.R.G.; Perry, N.B. (New Zealand Plant Protection, 2007)
Used in isolation several odour chemicals are known to increase trap capture of some thrips especially flowerinhabiting species This study examined the combined use of two structurally distinct odour chemicals both known to increase thrips trap capture in isolation Field bioassays using water traps were undertaken at two sites in New Zealand to target different thrips species Water traps had (1) no odour (water) (2) panisaldehyde only (3) methyl isonicotinate only (4) panisaldehyde and methyl isonicotinate mixed together in the same vial or (5) panisaldehyde and methyl isonicotinate placed separately in adjacent vials Thrips tabaci was the most common thrips species trapped at both sites (>92) Most odour treatments increased trap capture of T tabaci compared with the controls (panisaldehyde by 18 and 7 methyl isonicotinate by 5 and 30) but treatments with the two chemicals combined did not increase trap capture above the level of methyl isonicotinate alone at both sites